Blood coagulation factors and platelet response to drug‐induced hepatitis and hepatosis in rats. Issue 1 (27th December 2022) - Korolova, Daria; Gryshchenko, Viktoriya; Chernyshenko, Tamara; Platonov, Oleh; Hornytska, Olha; Chernyshenko, Volodymyr; Klymenko, Pavlo; Reshetnik, Yevdokiia; Platonova, Tetyana
Abstract: Background: Knowing the variability of blood coagulation responses to liver damage of different origins can provide a key to curing liver tissues or to mitigating treatment side effects. The aim of the present work was to compare the changes in the main components of hemostasis under experimental drug‐induced hepatosis and hepatitis in rats. Methods: We modeled diclofenac‐induced hepatitis and tetracycline‐induced hepatosis. Hemostasis response was gauged by measuring fibrinogen, factor X, protein C (PC), and prothrombin in plasma. The decarboxylated form of prothrombin was detected by measuring prothrombin index and ecamulin index. Platelet reactivity was studied using aggregometry. Results: Both hepatitis and hepatosis decreased the synthesis of fibrinogen, factor X, and prothrombin. However, protein carboxylation was not disrupted in hepatosis but was much impaired in hepatitis. PC decreased in both models as a consequence of its consumption possibly during inflammatory response. Platelet aggregation rate was lower in hepatosis but higher in hepatitis. Conclusions: Our findings imply the need for a thorough monitoring of the hemostasis system in liver diseases to avoid possible thrombotic complications. Its state indicates the disorder's rate and character. Abstract : Head‐to‐head comparison of hemostasis system parameters at drug‐induced hepatitis vs hepatosis in rats was performed. It was assumed that hemostasis system parameters should be monitored thoughtfully during liver diseases to avoid possible thrombotic complications and information about hemostasis system conditions can indicate the rate and character of liver disorders.